Real-time white light pseudocolor density encoder - Arizaga, Ricardo (1982)
A simple method for pseudocolor encoding of gray level information is proposed. It is based on the real-time addition of the positive and negative images of an object transparency, each one obtained in a different color. Conventional white light lamps with adequate color filters are used. Some experimental results are shown.